Uneasy lies the crown [large type] - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2019)
"In Uneasy Lies the Crown, the thrilling new mystery in Tasha Alexander's bestselling series, Lady Emily and her husband Colin must stop a serial killer whose sights may be set on the new king, Edward VII. On her deathbed, Queen Victoria asks to speak privately with trusted agent of the Crown Colin Hargreaves, slipping him a letter with her last, parting command: Une sanz pluis. Sapere aude. "One and no more. Dare to know." The year is 1901 and the death of Britain's longest-reigning monarch has sent all of the Empire into mourning. But for Lady Emily and her dashing husband Colin, the grieving is cut short as another royal death takes center stage. A body has been found in the Tower of London, posed to look like the murdered medieval king Henry VI. Soon after a second dead man turns up in London's exclusive Berkeley Square, his mutilated remains staged to evoke the violent demise of Edward II, it becomes evident that the individual behind the crimes plans to kill again and again. The race to find him takes Emily deep into the capital's underbelly, with its secret gangs, street children, and sleazy brothels. But the clues aren't adding up, and even more puzzling are the anonymous letters Colin has been receiving since Victoria's death. Is someone threatening her successor, Edward VII?"--